Correct Answer - Option 4 : Always TRUE when q is TRUE
(p → q) → r is a contradiction which is possible only when r is false and (p → q) is true.
Now, from here we can clearly say that option 4 is correct as (r → p) → q means ¬ (r → p) ∨ q.
Since r is false, (r → p) is true and ¬ (r → p) becomes false.
So, it becomes (false ∨ q). Now it totally depends on q. Whenever q is true, this value will always be true.
Alternate Method:
Let X ≡ p → q, Y ≡ (p → q) → r ≡ X → r,
Z ≡ r → p and W ≡ (r → p) → q ≡ Z → p
Using Truth table
p
|
q
|
r
|
X
|
Y
|
Z
|
W
|
0
|
0
|
0
|
1
|
0
|
1
|
0
|
0
|
0
|
1
|
1
|
1
|
0
|
1
|
0
|
1
|
0
|
1
|
0
|
1
|
1
|
0
|
1
|
1
|
1
|
1
|
0
|
1
|
1
|
0
|
0
|
0
|
1
|
1
|
0
|
1
|
0
|
1
|
0
|
1
|
1
|
0
|
1
|
1
|
0
|
1
|
0
|
1
|
1
|
1
|
1
|
1
|
1
|
1
|
1
|
1
|
So, from truth table also, it is clear that (r → p) → q is always true when q is true, and Y is false.